2006
DOI: 10.1002/adma.200600049
|View full text |Cite
|
Sign up to set email alerts
|

Periodical Variation of Electronic Properties in Polyhydroxylated Metallofullerene Materials

Abstract: Endohedral metallofullerenes (fullerenes with metal atom(s) encapsulated), as a novel form of carbon-related materials, [1] have attracted special attention for their potential applications [2][3][4][5][6][7][8][9][10] in electronic devices, [2,3] biomedical fields such as therapeutic medicine, [4,5] and a new generation of magnetic resonance imaging (MRI) contrast agents, [6][7][8] etc.Recently, the polyhydroxylated Gd@C 82 material was found to possess a very high efficiency of inhibiting cancer growth in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…1C). Protonation or deprotonation of [Gd@C 82 (OH) 22 ] n varies the negative charges of the hydroxyl groups, which further modulates the repulsive static electric forces among the [Gd@C 82 (OH) 22 ] n species (28). These repulsive static-electric forces could affect the size of hydrophobic-forceinduced self-assembly of [Gd@C 82 (OH) 22 ] n nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…1C). Protonation or deprotonation of [Gd@C 82 (OH) 22 ] n varies the negative charges of the hydroxyl groups, which further modulates the repulsive static electric forces among the [Gd@C 82 (OH) 22 ] n species (28). These repulsive static-electric forces could affect the size of hydrophobic-forceinduced self-assembly of [Gd@C 82 (OH) 22 ] n nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Some characterizations of water-soluble Gd@C 82 (OH) 22 nanoparticles were as described previously [8,[12][13][14][15][16]. Gd@C 82 (OH) 22 product was identified by a matrixassisted laser desorption time-of-flight mass spectrometer (MADLI-TOF-MS), and the structure was determined using infrared spectroscopy and nuclear magnetic resonance (NMR).…”
Section: Gd@c 82 (Oh) 22 Nanoparticle Characterizationmentioning
confidence: 99%
“…Gd@C 82 (OH) 22 nanoparticles were synthesized and characterized as described previously [8,[12][13][14][15][16]. The average number of hydroxyls was 22 as determined by XPS, and a schematic drawing of a Gd@C 82 (OH) 22 molecule was shown in Fig.…”
Section: Structure and Characterization Of Gd@c 82 (Oh) 22mentioning
confidence: 99%
“…It possesses a virus-like nanostructure, consisting of a magnetic metal core of a gadolinium (Gd) atom and a closed outer nanosheath of carbon atoms, which are further modified by about 22 outermost hydroxyl groups ( Figure 1) [9]. Several studies have found that the composition and numbers of the outer groups are largely responsible for the bioactive properties of fullerenol molecules [5,7,[14][15][16][17][18]. The Gd@C 82 (OH) 22 molecule is smaller than 2 nm, but Gd@C 82 (OH) 22 tends to aggregate in aqueous solutions and forms dispersed Gd@C 82 (OH) 22 nanoparticles with an average diameter of about 100 nm, which is a ubiquitous property identified in metallofullerenol studies [7].…”
Section: Characterizationmentioning
confidence: 99%